From the Simple to the Complex: Three Decades of the Analysis of Regional Convergence - Rojas-Rivera, Angela Milena; Rengifo-López, Juan Camilo (Sociedad y Economía, 2021)
The objective of this article is to provide an overview of the research on the neoclassical convergence hypothesis in Colombia. To this end, a survey of the international and national literature is carried out, in which the former contextualizes the latter. It also highlights the connection of the findings with regional development policies. It is found that in the studies on Colombian regional convergence traditional analysis has been the predominant method while the analysis of distributive dynamics and spatial effects has had the lowest incidence. Similarly, a slow entry of the endogenous growth theories and New Economic Geography is verified. In the absence of regional income convergence, evidenced at least since the 1990s and polarization in their distribution, policy recommendations are oriented towards activism through public spending and investment as well as the design of spatially differentiated interventions.